Suburbano območje mesta Celja - Radišek, Jure (Geografski vestnik, 2007)
The article shows the intensity of the process of suburbanisation in the hinterland of the town Celje. Suburban region is spreading continually from the suburbs to the agrarian landscape and the effects of suburbanization are seen in the changed sociogeographical, economic-geographical and physical appearance of the settlements.
Keywords: mesta; urbanizacija; suburbanizacija; Celje